Contribution of Swamp Buffalo Farms and Coconut PlantationsPalm Oil on the Income Structure of Farmer Households in Kuripan District, Barito Kuala Regency - Prawitasari, Melisa; Sriwati; Rochgiyanti; Pratama, Muhammad Rizki; Oktaviani, Nadia; Putri, Ni Made Febrianti Eka (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
Work as a buffalo breeder has been developed for generations in Kuripan District, Barito Kuala Regency, South Kalimantan Province. Swamp buffalo farming has become the main source of livelihood for livestock farmers and provides large profits. Since the existence of nucleus and plasma oil palm plantations, the living space for swamp buffalo has been reduced. This research was conducted with the aim of determining the contribution of swamp buffalo farming and oil palm plantations to the structure of household income in Kuripan District, Barito Kuala Regency, South Kalimantan Province. The research was conducted using qualitative methods. For data collection purposes, data sources were determined purposefully and snowball. Data collection techniques were carried out using observation, interviews and documentation. Data analysis is carried out continuously while in the field. The process of data collection and presentation is carried out based on the stages of data reduction, data display and data verification. The research results show that swamp buffalo farming as the main livelihood has contributed to the household income structure of the breeders.